ANALISIS VARIASI BAHASA GURU MUDA DI TIKTOK EDUKASI BAHASA INDONESIA: KAJIAN SOSIOLINGUISTIK - Meriska Vincensia Purba; Beslina Afriani Siagian; Monalisa Frince S (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to describe the language variations used by young teachers in Indonesian language educational content on TikTok, analyze the social and pedagogical factors that influence them, and examine their implications for learning in the digital age. This study employed a descriptive qualitative method. The data consisted of teacher utterances in 14 videos from three TikTok accounts: @syhraal, @faiqotulhima, and @guru_yr, totaling 36 utterances. Data were collected through documentation, free listening and conversation (SBLC), and note-taking techniques. The results indicate that teachers use language variations in the form of non-standard language, casual greetings, interjections, expressive particles, and pedagogical language, reflecting a blend of formal and informal styles in digital learning communication. This language variation is influenced by social factors (age, social relationships, and interaction context) as well as pedagogical factors related to the function of language in learning. The use of communicative and interactive language has been shown to increase audience engagement and understanding. This research contributes to the study of digital sociolinguistics by enhancing understanding of the use of language variations in social media-based learning, particularly the communication practices of young teachers on TikTok. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan variasi bahasa yang digunakan oleh guru muda dalam konten edukasi bahasa Indonesia di TikTok, menganalisis faktor sosial dan pedagogis yang memengaruhinya, serta mengkaji implikasinya terhadap pembelajaran di era digital. Penelitian ini menggunakan metode kualitatif deskriptif. Data berupa tuturan guru dalam 14 video dari tiga akun TikTok, yaitu @syhraal, @faiqotulhima, dan @guru_yr, dengan total 36 tuturan. Data dikumpulkan melalui teknik dokumentasi, simak bebas libat cakap (SBLC), dan teknik catat. Hasil penelitian menunjukkan bahwa guru menggunakan variasi bahasa berupa bahasa nonbaku, sapaan santai, interjeksi, partikel ekspresif, dan bahasa pedagogis yang mencerminkan perpaduan ragam formal dan informal dalam komunikasi pembelajaran digital. Variasi bahasa tersebut dipengaruhi oleh faktor sosial (usia, relasi sosial, dan konteks interaksi) serta faktor pedagogis yang berkaitan dengan fungsi bahasa dalam pembelajaran. Penggunaan bahasa yang komunikatif dan interaktif terbukti mampu meningkatkan keterlibatan dan pemahaman audiens. Penelitian ini berkontribusi pada kajian sosiolinguistik digital dengan memperkaya pemahaman tentang penggunaan variasi bahasa dalam pembelajaran berbasis media sosial, khususnya pada praktik komunikasi guru muda di TikTok.